Differential effect of baclofen on cortical and spinal inhibitory circuits - Stetkarova, Ivana; Kofler, Markus (Clinical neurophysiology, 2013)
OBJECTIVE: The cutaneous silent period (SP) is a spinal inhibitory reflex, which suppresses activity in spinal motor nuclei. Transcranial magnetic stimulation (TMS) elicits a cortical SP, which represents GABA(B) receptor-mediated inhibition of cortical excitability. Baclofen as a strong GABA(B) agonist effectively reduces muscle hypertonia, however, it is not known whether intrathecal baclofen (ITB) may modulate spinal inhibitory circuits. METHODS: We evaluated clinical and neurophysiological effects of ITB in ten patients with severe spasticity due to spinal cord injury (n = 9) and chronic progressive multiple sclerosis (n = 1). Neurophysiological assessment included H reflex and cutaneous and cortical SPs, before and 15, 30, 60, 90, 120, and 180 min after ITB bolus administration. RESULTS: ITB suppressed soleus H reflex as early as 15 min after lumbar bolus injection; MAS scores declined after 1 h. Cortical SP end latency and duration increased progressively with a significant maximum 3h following ITB bolus, whereas cutaneous SP latency and duration did not change significantly. CONCLUSION: The present findings suggest that baclofen does not affect the cutaneous SP, but prolongs the cortical SP. SIGNIFICANCE: The spinal inhibitory circuitry of the cutaneous SP is not modulated by GABA(B) receptor-mediated activity, in contrast to the cortical inhibitory circuitry of the cortical SP, which is subject to powerful GABA(B) control.
Keywords: Humans; lidé středního věku; Multiple Sclerosis; Spinal Injuries; Baclofen; Female; Reflex; dospělí; poranění páteře; lidé; míšní nervy; mozková kůra; časové faktory; Cerebral Cortex; H-reflex; Adult; kosterní svaly; agonisté receptorů GABA-B; H-Reflex; ženské pohlaví; Reaction Time; roztroušená skleróza; reflex; Male; Middle Aged; Muscle Spasticity; Muscle, Skeletal; reakční čas; svalová spasticita; Spinal Nerves; GABA-B Receptor Agonists; baklofen; mužské pohlaví; Time Factors; spinální injekce; Injections, Spinal